Symptomizing Crises. Theatres of the Pandemic – Isolated But Open and Inside/Outside - Lorek-Jezińska, Edyta (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2023)
My aim in this article is to look into manifestations of the corona crisis in theatre and performance as well as representations of other conflicts and problems, revealed or intensified by the pandemic. Drawing upon theories on the social influence of the pandemic developed by Snowden, Žižek and Neiman, I examine the potential of the pandemic theatre to critique and change the existing structures and to envision a more caring and considerate society. My analysis focuses on two British theatre projects: Inside/Outside: Six Short Plays (2021) and Isolated But Open: Voices from Across The Shutdown (2020) and their representations of the conflicted reality of the pandemic, addressing the questions of limitations and restrictions of rights and freedoms, on the one hand, and care and protection, on the other. The plays expose the conflicts between survival and life worth living, inside and outside, and the problems of the new normal and its life-changing potentials.